Compliance to Brazil's Forest Code will not protect biodiversity and ecosystem services. Issue 4 (28th December 2017) - Vieira, Raísa Romênia S.; Ribeiro, Bruno R.; Resende, Fernando M.; Brum, Fernanda T.; Machado, Nathália; Sales, Lilian Patrícia; Macedo, Lara; Soares‐Filho, Britaldo; Loyola, Rafael
Abstract: In striking contrast to heartening events in the adjacent Amazon, Brazil's Cerrado biome has seen continued deforestation over the past decade. Though approved in 2012, no study evaluated the impacts of new Brazilian Forest Code (FC) revision on biodiversity and ecosystem services. Here, we report the first assessment of the likely loss and gain in biodiversity and ecosystem services expected if the FC is properly enforced across 200 million hectares of the Cerrado. We also discuss the challenges associated to compliance with the law and present opportunities for conservation. Establishing restoration programmes in private properties with currently less native vegetation than required by the FC could create habitat for 25% more threatened species than now found in these places and could also increase water security and carbon stock in 56.6 MtC. More important, trading environmental reserve quotas coupled with the strategic expansion of protected areas on private and public land could definitely rescue the Cerrado from the brink.